The Multinational Enterprise Revisited The Essential Buckley and Casson - Buckley, P. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
The key writings by the authors on the future of the multinational enterprise published over the last thirty years. It contains seminal pieces with a new introduction and conclusion to tie these pieces together in a comprehensive overview of the theory of the multinational enterprise.